La regulación de los efectos laborales de la subcontratación: el Perú en América del Sur - Sanguineti, Wilfredo (2012)
The regulation of the labor effects of subcontracting:Peru in South AmericaThis article aims to place the operated changes in legal treatment of labor effects of the outsourcing of productive activities in Peru within the context of a more general trend to regulate this phenomenon operated in several countries in South America in a coincident way, in order to identify their points of coincidences and their singularities. It also questions the aptitude of regulatory solutions introduced to face up to problems generated by the new productive model which express these practices and it testsproposals to overcome in the future their weaknesses